2008
DOI: 10.1136/bjsm.2007.043604
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in schoolchildren and its relation to adiposity, physical activity, aerobic fitness and habitual diet

Abstract: Elevated CRP was evident in this cohort; however, whether high CRP levels during childhood and adolescence leads to an increased risk of CVD in later life has not been determined. Adiposity was related to CRP concentration, suggesting that reducing adiposity may be effective in lowering CRP and preventing future cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 35 publications
5
33
4
Order By: Relevance
“…Although no significant association of CRP with gender and age was observed, there was a higher prevalence of high CRP among females and adolescents,which corroborateda study conducted with 164 adolescents in two schools in England that showed no significant differences in the CRP concentrations among boys and girls 21 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although no significant association of CRP with gender and age was observed, there was a higher prevalence of high CRP among females and adolescents,which corroborateda study conducted with 164 adolescents in two schools in England that showed no significant differences in the CRP concentrations among boys and girls 21 .…”
Section: Discussionsupporting
confidence: 76%
“…At individual level; however, the correlation between BMI and cardiovascular disease is not always simple due in part to differences in the fatty tissue deposits, overall rate of adipocyte dysfunction, tissue vascularity, and local level of inflammation 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several inves tigations have compared the effect of dietary carbohydrate on concentra tion of inflammatory markers. One study found no association between diet compositions and serum CRP [6]; another found that a lowcarbohydrate diet increased serum CRP [16]. In a third study, the effect of lowcarbohy drate diet on CRP concentration was consistent with our own observations [17].…”
Section: Fbs = Fasting Blood Sugar; Tc = Total Cholesterol; Hdl-c = Hsupporting
confidence: 79%
“…Several of the drugs used to treat hyperglycaemia and dyslip daemia can reduce concentrations of inflammatory markers [1]. Recently, some studies have shown inflam matory markers are associated with lifestyle factors including diet, adipose tissue, physical activity and cigarette smoking [6,7] and have suggested lifestyle modification may reduce the risk of inflammation and CVD [8]. Accordingly, this study was aimed at investigating the association between modifiable lifestyle factors with inflam matory markers in patients with meta bolic syndrome in order to gain a better understanding of the factors that cause this phenomenon and prevention of CVD in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, once body fat was entered in the regression models, no associations with cardiovascular fitness or physical activity and either of the inflammatory markers measured were observed (74) . Similarly, no associations were found between cardiorespiratory fitness or selfreported physical activity and CRP in 12-year-old healthy Welsh children (75) . CRP, C3 and ceruloplasmin (but not C4) were negatively associated with muscle strength after controlling for sex, age, pubertal status, weight, height, socioeconomic status and cardiorespiratory fitness, but did not remain when adjusting body fat.…”
Section: Middle-aged Younger Adults and Childrenmentioning
confidence: 90%